KRIYA TEKSTIL TIE-DYE (IKAT CELUP): SEBUAH MEDIA EKSPLORASI ESTETIS YANG POPULER - Widodo, Suryo Tri (CORAK, 2012)
Tie-dye becomes the one of the most popular craft textile, which is known almost all over the world including in Indonesia. Making motif on to the fabric using tie-dye techniques is very easy to be learned, beside there are many kind of simple technics on it. These techniques are very unique and could be developed and explored without limited. The unpredictable effects of motifs sometimes may appear and can be resulted from tie-dye techniques. In this article we will study about tie-dye in many aspect i.e. term of tie-dye, tradition and culture background of tie-dye, mainly showing about tie-dye techniques, and a few tie-dye products. This paper expected give the wide describing and inspiring about tie-dye in craft textile works or tiedye as an expression of fine art.Keywords: tie-dye, resist-dye, textile motif, craft textile, aesthetic exploration